The making of the Bible from the first fragments to sacred scripture - Schmid, Konrad 1965-; Schröter, Jens 1961-; Lewis, Peter 1958- (Cambridge Harvard University Press, 2021)
Cover -- Title Page -- Copyright -- Contents -- 1. What Is "the Bible"? -- 2. Scribal Culture -- 3. Emerging Judaism -- 4. Scripture in Judaism -- 5. Ancient Jewish Texts in Early Christianity -- 6. The Formation of the Christian Bible -- 7. The Jewish Bible, the Mishnah, and the Talmud -- 8. The Book of Books -- Abbreviations -- Notes -- Bibliography -- Acknowledgments -- Illustration Credits -- Scripture Index -- General Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books